Implementing the Value of Character Education in Islamic Religious Education in State Elementary School (SDN) Ciranjang 02 Cianjur - Nur Azizah (GoAcademica Research & Publishing, 2022)
The importance of education for human life causes the need to educate human character from an early age. This character planting can then be done through various media, where Islamic religious education media can be considered entirely appropriate as a medium for planting character education values. This study aims to see how the importance of character education is instilled through learning Islamic religious education at SDN Ciranjang 02. This research will be carried out using a descriptive qualitative approach. The data from this study were obtained from various research results and previous studies. This study found that there were seven aspects of learning Islamic religious education at SDN Ciranjang 02 Cianjur. Then the implementation of character education is carried out by getting used to religion that is contrary to the Qur’an and As-Sunnah. Finally, the implementation of character education through Islamic Religious Education learning at SDN Cirajang 02 is integrated into the Islamic Religious Education subjects, especially in monotheism and morality.